Metal regeneration during an ex-situ disturbance experiment on deep-sea sediments from the polymetallic nodule area of western Pacific - Yang, Juan; Xing, Zhaohui; Liu, Baolin; Sun, Dong; Wang, Chunsheng; Han, Luwei; Xia, Jianxin; Zhang, Wenquan; Song, Chengbing (Frontiers in Marine Science, 2024)
The ecological implications of deep-sea mining, particularly the considerable discharge of suspended sediments during operational processes, have attracted substantial concerns. In order to reveal the metal regeneration dynamics in the polymetallic nodule area of the western Pacific Ocean, ex-situ sediment disturbance experiments were conducted on a research vessel. After two levels of regulated stirring disturbance were exerted for half an hour, the concentrations of 12 dissolved metals and physicochemical parameters, including Eh and pH, were monitored continuously in the overlying water for three days. Porewater samples were also collected at the starting and ending time of each experiment to detect the change of dissolved metal profiles within the sediments. The findings revealed that the sediment disturbance led to fluctuations in the concentrations of metals in the overlying water, with manganese exhibiting the most pronounced change at a coefficient of 208%. The temporal patterns of dissolved metal concentrations demonstrated a coherent behavior among certain metals, such as Li, V, Co, Ni, Rb, Mo, and Cs, which displayed an overall increase, ultimately surpassing the initial concentrations in the overlying water. In line with this, the metal concentration profiles in the porewater were also elevated. Spearman correlation analysis confirmed the synchronized behavior of these metals. The results suggested that the metals mobility might be governed by physicochemical factors in the overlying water. Moreover, the sedimentary features, such as grain size composition, and the morphological state of metals in sediments played pivotal roles in the differential responses of metal groups to sediment disturbance across stations. Conversely, the disturbance intensity was found to have a relatively minor impact on the dissolved metal behavior. The findings from the ex-situ experiments provided critical insights for predicting metal regeneration related to deep-sea mining, which are expected to be validated through rigorous monitoring protocols during future in-situ mining trials.